A detailed study on context-aware architectures in internet of things. (5th March 2021) - Deeba, K.; Saravanaguru, RA.K.
Internet of things (IoT) is used to get the data around the world at your fingertip. As we move towards IoT the role of sensors has become vital. These sensors generate a vast amount of data. Sensors are used to sense and collects parallel information from the given set. We propose context-aware for IoT architectures which computerise the task. In this paper, we will discuss about the architecture of context-aware, IoT and context-aware reasoning. The principal objective of this paper is to audit existing architecture identified with context-aware and IoT and to make the comparative analysis table. The principal point is to enable the clients to present the issues and our proposed design enhances and delivers important information.